Bailey & Love's Short practice of surgery. - Bailey, Hamilton, 1894-1961.; hamilton bailey, 1891-1974.; Mann, Charles V.; Russell, R. C. G. (london : Chapman & Hall Medical, 1992)
this book have recognised the impact of civil trauma by a new chapter on accident and emergency surgery.
healing and management of wounds -- accident and emergency surgery-- lymphatic disorders --diseases of bones and joints-- the larynx-- the thorax.
surgery . includes index.
Includes bibliographical references and index.
All age.
Keywords: Surgery